Cell types and structures involved in tench, Tinca tinca (L.), defence mechanisms against a systemic digenean infection. Issue 6 (7th January 2013) - Dezfuli, B S; Lui, A; Pironi, F; Manera, M; Shinn, A P; Lorenzoni, M
Abstract Histopathological and ultrastructural investigations were conducted on 36 tench, Tinca tinca (L.), from Lake Trasimeno (Italy). The gills, intestine, liver, spleen, kidney and heart of 21 individuals were found to harbour an extensive infection of larvae of an unidentified digenean trematode. The eyes, gonads, swim bladder and muscles were uninfected. The parasites in each tissue type were embedded in a granulomatous proliferation of tissue, forming a reactive fibroconnective capsule around each larva. Most of the encysted larvae were metacercariae, in a degenerative state, but on occasion some cercariae were found. Many of the granulomas were either necrotic or had a calcified core. Within the granuloma of each, the occurrence of granulocytes, macrophages, rodlet cells and pigment‐bearing macrophage aggregates was observed. Hearts bore the highest parasitic infection. Whilst the presence of metacercariae within the intestine was found positioned between the submucosa and muscle layers, metacercariae in the liver were commonly found encysted on its surface where the hepatocytes in close contact with the granuloma were observed to have electron‐lucent vesicles within their cytoplasm. Metacercariae encysting adjacent to the cartilaginous rods of gill filaments were seen to elicit a proliferation of the cartilage from the perichondrium. Rodlet cells, neutrophils and mast cells were frequently observed in close proximity to, and within, infected gill capillaries. Given the degenerated state of most granulomas, a morphology‐based identification of the enclosed digeneans was not possible.